X-ray phase and microstructural analysis of hardening coatings obtained by self-propagating high-temperature synthesis in combination with heating of a mixture of based on high-frequency current treatment - Ishkov, A.A.; Malikov, V.N.; Tikhonsky, N.D.; Gulyarenko, A.A.; Remshev, E.Yu.; Voinash, S.A.; Sokolova, V.A.; Orekhovskaya, A.A. (KU Publ., 2022)
The paper describes the results of studies of hardening boride coatings obtained during the implementation of the process of self-propagating high-temperature synthesis. These coatings were composite materials based on aluminum oxide and boron. The obtained coatings were subjected to X-ray phase and microstructural analysis, which showed the main components of the resulting compositions and made it possible to assess the thickness and structure of the coating-base metal transition area. The different content of silicon and iron makes it possible to assess the occurrence of surface chemical and metallurgical processes during self-propagating high-temperature synthesis when heating of the base mixture samples on high-frequency current treatment. The expediency of using high-frequency current treatment in combination with the process of self-propagating high-temperature synthesis for better-quality spattering of the hardening coating is shown. The appearance of two areas in the coating with different thickness and structure of the coating is established.
Keywords: steel hardening; microstructure analysis; self-propagating high-temperature synthesis; coatings; highfrequency currents